High-temperature annealing of an iron microplate with excellent microwave absorption performance and its direct micromagnetic analysis by electron holography and Lorentz microscopy. Issue 24 (5th June 2017) - You, Wenbin; She, Wen; Liu, Zhengwang; Bi, Han; Che, Renchao
Abstract : Microplate iron exhibits excellent microwave absorption performance because of its special morphology and optimization of its magnetic property. Abstract : To meet the demand of electromagnetic interference shielding, cheap and easily available microwave absorbers are urgently required. Recently, most of the related research has been focussed on a number of complicated absorbers comprising multi-components because of their better electromagnetic match. However, it is still a great challenge to develop an absorber that simultaneously possesses the advantages of easy fabrication, low-cost, ultra-wide bandwidth, and strong absorption. Hence, development of a simple and convenient absorber with efficient performance is attracting significant attention because of the urgent requirement of this type of absorbers. Herein, a series of single-component iron-based absorbers with different morphologies and grain sizes was successfully prepared. Strong absorption intensity (∼−43.4 dB) was found in plate-like samples, which could even match those of some multi-component absorbers. Electron holography and Lorentz microscopy analysis were used for the further comprehension of the relationships among the microstructure, electromagnetic property, and microwave absorption performance. The primary grain size of the present iron microplate was found fundamentally important for microwave absorption performance. This cheap and available absorber is believed to be an optimal choice for single-component absorbers and useful in the research of absorption mechanism.